Chagas Disease Basic Investigations and Challenges - Nissapatorn, Veeranoot; Oz, Helieh S. (IntechOpen, 2018)
This book contains 11 chapters of significant and updated materials on what we know and what we lack and need in better understanding of Trypanosoma cruzi - a parasite that never dies - and the consequences of Chagas disease as one of the most important neglected parasitic diseases threatening the global health and wellbeing. This book is intended to increase the readers' enthusiasm to explore the four sections of the contents: Section 1 begins with biochemistry, pathophysiology, histo-immunological study, and findings to assist in the diagnosis; Section 2 further investigates the role of vector in propagation of the parasite, the intensity on epidemiology, and the severity on clinical aspects, which help us to be well perceived on the course of disease; Section 3 is seeking beyond modern medicine and what lays in the nature that helps fight against this parasite; and the last section, Section 4, deals with the impacts of public health problem and the control strategies on Chagas disease.